Hubungan Tingkat Pendidikan Ibu Dengan Perkembangan Anak Di Posyandu Mawar Monggang Bantul Yogyakarta Tahun 2022 - Widy Nurwiandani; Desi Ekawati (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
Background: The average length of education Indonesia is only 9 years old, it is equivalent to grade 3 junior. In terms of quality of HR (Human Resources) was approximately 60% and 80% of junior high school graduates. Establishment of the quality of Human Resources (HR) is optimal, either physically or psychologically dependent on the growth process of children at an early age. The rate of growth and development at any stage is not the same, depending on heredity, maternal education, nutrition consumption, treatment of parents and the child's environment. The behavior of parents,/ mother is one important factor in the sustainability of the growth and development of children. Figures health care coverage of children under five in Puskesmas Sewon 1 achieve the target of above 85%. Objective: To determine the relationship with the mother's educational level of child development at IHC Mawar Monggang Bantul Yogyakarta in 2022. Methods: This study used observational Analytical methods using cross-sectional approach. The population in this study are all mothers of children aged 0-59 months in IHC Mawar Monggang village area Bantul, Yogyakarta. The samples in this study using total sampling technique to test as many as 69.Then using correlation analysis Kendall Tau (τ). The tools used in this study is the data collection questionnaire. Results: The study maternal education level is obtained largely secondary education with appropriate child development as many as 35 respondents (83.3%) and 7 respondents (16.7%) with a child's development is dubious. The correlation coefficient is 0523 with a significance of 0.001 (ρ <0.05). Conclusion: There is a positive relationship between the level of education being a mother with the development of children aged 0-59 months in IHC Mawar Monggang Bantul Yogyakarta in 2022, and statistically meaningful Keywords: Education Level Mother, Child Development